Identifying Parathyroid Glands With Carbon Nanoparticle Suspension Does Not Help Protect Parathyroid Function in Thyroid Surgery: A Prospective, Randomized Control Clinical Study. (August 2016) - Liu, Xu; Chang, Shi; Jiang, Xiaolin; Huang, Peng; Yuan, Zhengtai
Objective . We aim to evaluate the technique of identifying parathyroid glands with carbon nanoparticle suspension (CNPS) in thyroid surgeries from the perspectives of degrees of declining intact parathyroid hormone (iPTH), operation time, and time of postoperative stay. Methods . A total of 156 patients who underwent thyroid surgeries in General Surgical Department of Xiangya Hospital between May 2012 and May 2015 were involved in the study. A total of 78 patients were injected with CNPS during the surgery (CNPS group); the other 78 patients received normal saline (control group). Cases were classified into 3 surgical approaches: conventional partial thyroidectomy, conventional total thyroidectomy, and endoscopic partial thyroidectomy. Degrees of declining iPTH were tested to determine the severity of parathyroid injury. Operation time and postoperative hospital stay time were recorded. A P value of less than .05 was considered statistically significant. Results . For levels of declining iPTH, there was no statistically significant (ss) difference in conventional thyroid surgery. In endoscopic partial thyroidectomy, it was 23.37 ± 16.20 versus 11.94 ± 11.23 pg/mL ( P = .02, ss). The operation time of conventional total thyroidectomy was 210.10 ± 83.75 versus 164.84 ± 69.22 minutes ( P = .03, ss), while it was 193.04 ± 75.53 versus 127.67 ± 60.06 minutes ( P = .007, ss) in endoscopic thyroidectomy. Conclusions . CNPS is not beneficial for protecting the function of parathyroid gland in thyroid surgery from the perspective of declining iPTH. Applying CNPS in conventional total thyroidectomy and endoscopic partial thyroidectomy will also lead to significantly prolonged operation time.